PCR amplification of a long rDNA segment with one primer pair in agriculturally important nematodes - Carta, L. K. (J Nematol, 2019)
Ribosomal DNA has been a reliable source of taxonomic and phylogenetic markers due to its high copy number in the genome and stable variation with few polymorphisms due to the homogenizing effect of concerted evolution. Typically specific regions are amplified through polymerase chain reaction (PCR) with multiple primer pairs that generate often incomplete and overlapping regions between adjacent segments of 18S, ITS1, 5.8S, ITS2, and 28S rDNA nucleotide sequences when combined in tandem. To improve the efficiency of this effort, a strategy for generating all these molecular sequences at once through PCR amplification of a large ribosomal 3.3 to 4.2 kb DNA target was developed using primer 18S-CL-F3 paired with D3B or a new alternative 28S PCR primer (28S-CL-R) and other well-positioned and ribosomal-specific sequencing primers (including novel primers 18S-CL-F7, 18S-CL-R6, 18S-CL-R7, 18S-CL-F8, 5.8S-CL-F1, 5.8S-CL-R1, 28S-CL-F1, 28S-CL-R3, 28S-CL-F3, 28S-CL-R1, and 28S-CL-F2). The D1 region between ITS2 and 28S boundaries and the flanking sequence between 18S and ITS1 boundaries were fully revealed in this large nucleotide segment. To demonstrate the value of this strategy, the long rDNA segment was amplified and directly sequenced in 17 agriculturally important nematodes from the Tylenchida, Aphelenchida, and Dorylaimida. The primers and their positions may be employed with traditional Sanger sequencing and with next-generation sequencing reagents and protocols.